THE ROLE OF INFORMATION TECHNOLOGY IN THE TRAINING OF FUTURE ASTRONOMY TEACHERS - Мохун, Сергій; Кульчицький, Роман (Modern engineering and innovative technologies, 2024)
The issue of using information technologies in teaching astronomy to students of pedagogical institutions of higher education is important and relevant today. It follows that special training of future teachers in the use of new information technologies